POCHAYIV LAVRA IN THE PERIOD OF ACQUISITION OF AUTOCEPHALY BY UKRAINIAN ORTHODOX CHURCH: POSITION, DEMONSTRATION OF REACTION, PROSPECTS - Rychko Viktoriya (International Journal of Innovative Technologies in Social Science, 2020)
The article studies the reaction of famous monastic vow in Ukraine – The Holy Dormition Pochayiv Lavra on the acquisition of autocephality by Ukrainian Orthodox. Through the lens of facts proving its activity, it is explained that in the activation process of getting tomos of autocephality by the Orthodox Church of Ukraine, Pochayiv Lavra demonstrated the opposition to initiatives, directed at the formation of Ukrainian Orthodox national character. The document, which officially declared it, was “Address of Metropolitan Volodymyr, Father Superior of the Holy Dormition Lavra, regarding risk and “tomos””. The destructive activity of Pochayiv Lavra concerning the problem of overcoming the Orthodox conflict in Ukraine was demonstrated in mobilization of its piligrims to the participation in the acts that were pseudo-protest movements in nature, which were aimed at the destabilization of Ukrainian society and activation of intrapublic protests. In the end it could have been the reason not only for the interruption or even cancellation of the religious and church project of acquiring the status of Local Church by Ukrainian Orthodox Church, but in wider context – the significant slowdown of the consolidation of Ukrainian society and rollout of its national identity accumulation process.